2009
DOI: 10.2353/ajpath.2009.080517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Signaling Systems in Proliferating and Involuting Phase Infantile Hemangiomas by Genome-Wide Transcriptional Profiling

Abstract: Infantile hemangiomas are characterized by rapid capillary growth during the first year of life followed by involution during early childhood. The natural history of these lesions creates a unique opportunity to study the changes in gene expression that occur in the vessels of these tumors as they proliferate and regress. Here we use laser capture microdissection and genome-wide transcriptional profiling of vessels from proliferating and involuting hemangiomas to identify differentially expressed genes. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 61 publications
5
63
1
Order By: Relevance
“…Previous studies have demonstrated that the IH life-cycle is associated with clear spatialtemporal changes in the expression of Notch members [14,15]. We analyzed the expression levels of Jagged1, Notch3, Hes1 and HEYL in proliferating and involuting IHs using real-time PCR (Fig.…”
Section: Notch3 Hes1 and Heyl Were Highly Expressed In Involuting Hementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the IH life-cycle is associated with clear spatialtemporal changes in the expression of Notch members [14,15]. We analyzed the expression levels of Jagged1, Notch3, Hes1 and HEYL in proliferating and involuting IHs using real-time PCR (Fig.…”
Section: Notch3 Hes1 and Heyl Were Highly Expressed In Involuting Hementioning
confidence: 99%
“…Current data suggest that several Notch components are involved in the pathogenesis of IH [14][15][16][17]. Remarkably, recent studies have revealed that endothelial-derived Jagged1 can induce hemangioma-derived stem cells (HemSCs) to acquire a pericyte-like phenotype, which is a crucial step in the vasculogenesis of IH.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of VEGFR-1 expression has been implicated in the proliferation of infantile HemECs and tissue [40,52]. The mechanism for this low expression in HemECs was shown to be the sequestration of β1-inergrin in a multiprotein complex composed of tumor endothelial marker-8 (TEM8) and VEGFR-2, which inhibits nuclear factor in activated T cells (NFAT)-mediated VEGFR-1 transcription [40].…”
Section: Discrepancy Of Vegfr-1 Signaling In Hemscs and Hemecsmentioning
confidence: 99%
“…Our statistical analyses were not designed to unravel the differences between the stages of infantile hemangiomas but, studies that did, determined them to differ with regard to the genes of the chronic inflammatory response and of the NOTCH pathway. 4,27 For pyogenic granuloma, correspondence analysis and analysis of variance revealed only dissimilarities with the other tissues tested. Such specific genetic behavior of vessels from pyogenic granuloma was not surprising, although not previously described.…”
Section: Modern Pathology (2013) 26 247-255mentioning
confidence: 97%
“…4 Array Hybridization RNA was extracted and amplified using the Paradise Reagent System Kit according to the manufacturer's recommendations (Paradise Reagent System Kit, Applied Biosystems). The amplified and purified cDNAs were then submitted to the Harvard-Partner Center for Genetics and Genomics Facility (www.hpcgg.org).…”
Section: Samplesmentioning
confidence: 99%